Technology in Islamic Education Curriculum: Challenges and Opportunities - Ubaedullah, Dudun; Rokimin; Suryono, Fajar (Jurnal Al Burhan, 2025)
The integration of technology into Islamic education is crucial for meeting the evolving needs of students in the digital age, aiming to enhance both academic and moral development while preserving Islamic values. However, several challenges hinder this integration, including inadequate infrastructure, limited teacher training, and resistance to new teaching methods. This study explores these challenges and identifies opportunities for integrating technology into the curriculum of Islamic Elementary Schools (Madrasah Ibtidaiyah) and Kindergartens (TK) in Indonesia. A systematic review following the PRISMA framework was conducted, analyzing nine articles out of 25,570. The study identified key barriers, such as limited access to digital devices and the internet, inadequate digital competency among teachers, and resistance to changes in traditional pedagogical methods. Despite these challenges, the study highlights opportunities to enhance student engagement and foster critical thinking through the use of interactive technologies, such as multimedia and AI. These technologies can bridge the gap between traditional Islamic values and modern educational practices. This study demonstrates the importance of continuous professional development for teachers, investment in digital infrastructure, and curriculum reform that integrates Islamic teachings with modern technology. A balanced approach is crucial to ensure the integrity of Islamic education while simultaneously harnessing the benefits of technological advancements. Future research should focus on developing strategies to address these challenges and maximize the potential of technology in Islamic teaching, ultimately improving student outcomes and engagement.